Music Belongs to Everyone: Moments of Progress in Community Music Therapy with Musicians with Severe Disabilities - Tiszai, Luca (Voices: A World Forum for Music Therapy, 2016)
The article describes novel and successful projects involving musicians with severe disabilities and adolescent music students. The Nádizumzuzum Orchestra consists of adult members of a nursing home. They are able to play music with a newly developed method called Consonate. The young musicians are students of the Zoltán Kodály Hungarian Choir School. This article presents the historical and socio-political background of the project to illustrate how music therapy grows from particular cultural and political circumstances of Hungary, and therefore takes a particular Hungarian form and flavour. The article also reflects on the wider context of the international research and practice of Community Music Therapy.